Development of the Microscopic Traffic Simulation Model with the Fuzzy Logic technique. (January 2013) - Errampalli, Madhu; Okushima, Masashi; Akiyama, Takamasa
Microscopic traffic simulation (MTS) has attracted increasing attention in the last two decades as it analyzes individual vehicle/driver behavior more precisely and realistically than other methods. MTS is nothing but a series of human decisions under various traffic situations. Since human element is involved at many stages of simulation, the possibility of approximation/error in the decisions would be high. In this direction, the fuzzy logic technique appropriately takes such approximations into account while modeling drivers' decisions. Some of the MTS models have considered fuzzy logic in at most one or two models, such as car following, lane change behavior, etc., with limited urban congested conditions. However, human involvement exists beyond these and realistic output from the simulation would not be possible unless the approximations involved at different stages are appropriately and simultaneously considered. In the present study, a Fuzzy Logic based Microscopic Traffic Simulation Model (FLoMiTSiM) to describe human behavior on the urban road network in many possible situations is proposed and appropriately validated using the observed data from the city of Gifu, Japan. To demonstrate the applicability and suitability of the proposed FLoMiTSiM, bus priority policies, namely bus lanes, are evaluated.